Structural analysis of the Leptospiraceae and Borrelia burgdorferi by high-voltage electron microscopy. - Goldstein, S F (1996)
Spirochetes are an evolutionary and structurally unique group of bacteria. Outermost is a membrane sheath (OS), and within this sheath are the protoplasmic cell cylinder (PC) and periplasmic flagella (PFs). The PFs are attached at each end of the PC and, depending on the species, may or may not overlap in the center of the cell. The precise location of the PFs within the spirochetal cells is unknown. The PFs could lie along the cell axis. Alternatively, the PFs could wrap around the PC in either a right- or a left-handed sense. To understand the factors that cause the PFs to influence cell shape and allow the cells to swim, we determined the precise location of the PFs in the Leptospiraceae (Leptonema illini) and Borrelia burgdorferi. Our approach was to use high-voltage electron microscopy and analyze the three-dimensional images obtained from thick sections of embedded cells. We found that a single PF in L. illini is located in a central channel 29 nm in diameter running along the helix axis of the right-handed PC. The presence of the PFs is associated with the end being hook shaped. The results obtained agree with the current model of Leptospiraceae motility. In B. burgdorferi, which forms a flattened wave, the relationship between the PFs and the PC is more complicated. A multistrand ridge 67 nm in diameter, which was shown to be composed of PFs by cross-sectional and mutant analysis, was found to extend along the entire length of the cell. We found that the PFs wrapped around the PC in a right-handed sense. However, the PFs formed a left-handed helix in space. The wavelength of the cell body and the helix pitch of the PFs were found to be identical (2.83 microm). The results obtained were used to propose a model of B. burgdorferi motility whereby backward-propagating waves, which gyrate counterclockwise as viewed from the back of the cell, are generated by the counterclockwise rotation of the internal PFs. Concomitant with this motion, the cell is believed to rotate clockwise about the body axis as shown for the Leptospiraceae.